SEBUAH PARADOKSAL KRISIS PANGAN DAN IRONI KETAHANAN PANGAN Tinjauan Perspektif Islam - *, Maryatin; *, Subiyanto (Prodi Ekonomi Syariah Pascasarjana IAIN Kudus, 2013)
Today the world is faced with major economic crisis. Including the food crisis. One way of dealing to the crisis with food security program, the State’s have rich food encounter crisis, this is a paradox. This research used library research to descriptive analysis, namely to assess the food crisis, food security according to the capitalist and how Islam according to food crisis or food security, called the Islamic perspective. In addition, this research the author uses qualitative research with collecting data from the literature which categorized to the primary and secondary data. How to get the data is obtained by reading leteratur books, papers, magazines, and research reports. To overcome the food crisis there is food security program. Food security according to capitalist consists of three main sub-systems is the availability, access and absorption of food. availability of food is the food in an amount sufficient nutrious and safe for all people in a country which derived either from own production, imports, food stocks and food aid was seen in macro. If the stock is adequate availability of food is considered sufficient. Similarly, access to food is not meant for any individual security can get food needs. It’s how people are able to meet their needs by producing their own, buy, or get help in order to buy. So which determines access to food is a distribution. This distribution is still based on the price mechanism as the capitalist economic doctrine. Islam considers that food security can be achieved by placing the concept of ownership is evident. food security in Islam include: (1) guarantee for compliance basic needs of food; countries that guarantee the basic needs of its people (2) food availability and affordability of food by individual communities, and (3) State of Food Independence.